Individual differences and personality - Ashton, Michael Craig, 1970- (Academic Press, 2013)
How do we come to be who we are? Why do we differ in our personalities? How do these differences matter in life? This textbook on Individual Differences and Personality aims to describe how and why personality varies between one person and the next. Unlike books that focus on individual theorists, this book focuses on current research and theory on the nature of personality and related individual differences. The book begins by discussing how personality is measured, the concept of a personality trait, and the basic dimensions of personality. This leads to a discussion of the origins of personality, with descriptions of its developmental course, its biological causes, its genetic and environmental influences, and its evolutionary function. The concept of a personality disorder is then described, followed by a discussion of the influence of personality on life outcomes in relationships, work, and health. Finally, the book examines in detail the important differences between individuals in the realms of mental abilities, of beliefs and attitudes, and of sexuality. Intended for courses in personality and individual differences, this book may also serve as a useful overview of personality research for academics in related fields. Singly authored for consistency of breadth, depth, and presentation, Individual Differences and Personality will engage students with its interesting boxed asides. Sample boxes describe a wide variety of topics, including such issues as cross-generational differences, personality in animals, personality and occupational choice, the role of the womb environment, and many others. In addition to covering the Big Five and HEXACO models of personality structure, the book also includes topics often left out of other personality books, including individual differences in mental abilities, religion, politics, and sexuality. There is also deep coverage of the biological bases of personality, including discussions of neurotransmitters, brain structures, and hormones. The explanation of genetic and environmental influences is made clear and straightforward, and the discussion of evolutionary function is unique among personality texts. Table of Contents: Introduction; Basic Concepts in Psychological Measurement; Personality Traits and the Inventories That Measure Them; Personality Structure: Classifying Traits; Developmental Change and Stability of Personality; Biological Bases of Personality; Genetic and Environmental Influences on Personality; The Evolutionary Function of Personality; Personality Disorders; Personality and Life Outcomes; Mental Ability; Religion and Politics; Sexuality; Conclusion. Integrates research findings with real life outcomes explaining why personality leads to successes or failures in life Discusses healthy personalities as well as personality disorders New chapter on vocational interests and personality 35% revised Well reviewed in its first edition Unique coverage of the evolutionary basis for personality Strong coverage of biology, genetics, neuroscience of personalityTestbank for professors.